2012
DOI: 10.1371/journal.pone.0047125
|View full text |Cite
|
Sign up to set email alerts
|

Novel AChE Inhibitors for Sustainable Insecticide Resistance Management

Abstract: Resistance to insecticides has become a critical issue in pest management and it is particularly chronic in the control of human disease vectors. The gravity of this situation is being exacerbated since there has not been a new insecticide class produced for over twenty years. Reasoned strategies have been developed to limit resistance spread but have proven difficult to implement in the field. Here we propose a new conceptual strategy based on inhibitors that preferentially target mosquitoes already resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Likewise, recent work targeting the catalytic serine residue with covalent inhibitors containing a carbamate functionality has shown that considerable selectivity ratios can be achieved for mosquito over vertebrate enzymes [ 31 , 32 , 54 , 61 ]. While the potential of covalent inhibitors has been investigated in a number of studies, inhibitors with a different mode of action, such as non-covalent inhibitors, are less well explored [ 62 ]. Another major concern in insecticide development is to overcome the increasing resistance to AChE inhibitors conferred by e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, recent work targeting the catalytic serine residue with covalent inhibitors containing a carbamate functionality has shown that considerable selectivity ratios can be achieved for mosquito over vertebrate enzymes [ 31 , 32 , 54 , 61 ]. While the potential of covalent inhibitors has been investigated in a number of studies, inhibitors with a different mode of action, such as non-covalent inhibitors, are less well explored [ 62 ]. Another major concern in insecticide development is to overcome the increasing resistance to AChE inhibitors conferred by e .…”
Section: Resultsmentioning
confidence: 99%
“…the G119S mutation. Novel small-core carbamates have been designed [ 54 ], and it has also been shown that it is possible to target resistant mutant enzymes with non-covalent inhibitors [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 The inhibition of acetylcholinesterase is the major mode of action for most insecticides especially organophosphates and carbamates, and this effect may be responsible for larvicidal activity on against Culex quinquefasciatus, Culex pipiens, Anopheles gambiae and Aedes aegypti. 16,17 In this context, the aims of this study was to obtain derivatives of carvacrol/thymol and to investigate the inhibitory activity of acetylcholinesterase and larvicidal against Aedes aegypti larvae. The synthesis of the compounds was carried out according to the procedure shown in Figures 1 and 2.…”
Section: -14mentioning
confidence: 99%
“…Downsampling and purchase of additional analogs led to the identification of seven barbaturic acid-furan or –thiophene analogs that inhibited G119S Cp AChE ≥10-fold more strongly than WT Cp AChE (e.g. 28 ) [68]. …”
Section: Specific Inhibitors Of G119s An Gambiae Achementioning
confidence: 99%